Membangun Kesadaran Multikultural bagi Siswa di SMKN 5 Gorontalo: Pengabdian - Roni Lukum; Abd. Firman Bunta; Safawi Juwono S.Rintih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to build multicultural awareness among students of SMK Negeri 5 Gorontalo through participatory and contextual learning activities. The program was carried out by involving lecturers, students, and teachers through several stages, including material delivery, group discussions, case studies, role-playing, creative workshops, and reflection sessions. This approach was designed to ensure that students not only understand the concept of multiculturalism theoretically but are also able to internalize the values of tolerance, cooperation, and mutual respect in their daily school life. Data were collected through field observations and questionnaires distributed to 104 students in the initial stage and 31 students during the final evaluation stage. The analysis results show an average increase of 30–35% across all indicators of multicultural awareness, particularly in aspects of cross-cultural interaction (P3), understanding of cooperation as a multicultural value (P7), and acceptance of linguistic diversity (P9). These improvements indicate that the program successfully transformed students’ mindsets from passive acceptance to reflective understanding and inclusive attitudes toward diversity. Thus, multicultural education has proven to be an effective means of shaping students’ character to become tolerant, adaptive, and capable of living harmoniously within a pluralistic society.